THE JOLI-JOLI’S GAME IN THE LEARNING WRITING POETRY: A CULTURALLY RESPONSIVE MEANINGFUL LEARNING MODEL - Dina Ramadhanti (Jurusan Sastra Indonesia, 2019)
Meaningful learning is assumed as one of the solutions to overcome various problems in literacy teaching. Meaningful learning is the learning arranged in accordance with the cognitive structure of the students so as to facilitate students to understand new information with the cognitive structure they have. One is the culture and environment of everyday students that are integrated into the learning process. With teachers integrating culture into the learning process means teachers have carried out culturally responsive teaching. Culturally responsive teaching is learning that uses diverse cultural characteristics, experiences, and ethnic perspectives of students as a channel for more effective teaching. One culture that can be integrated into the learning process, especially writing poetry is a game of Joli-Joli which is a game of children in the Minangkabau area. Joli-Joli games are integrated into meaningful learning steps to become meaningful models of culturally responsive teaching. In addition to enriching the vocabulary needed in writing poetry, joli-joli game also contains Minangkabau cultural values that are instrumental in the formation of student attitudes and characters.